Analisis Hubungan Iklim Keselamatan Kerja dengan Safety Behavior Pekerja di Sektor Industri Manufaktur, PT Tata Metal Lestari - Cindy Aprilia Setiawan (2021)
Unsafe action remain the main problem at PT Tata Metal Lestari with the highest incidence rate of 59% in August 2020. The aim of this study was to anlyze the association of safety climate and workers' safety behavior in the manufacturing industry sector, PT Tata Metal Lestari. This study used a quantitative method with a cross-sectional design. NOSACQ-5- questionnaires were used to collect data. The population involved in this study were 56 workers in the production unit. These workers were selected by using a purposive sampling technique. The results show that of 7 dimensions studied, 4 dimensions have a significant association with safety behavior which are management safety priority, commitment, and competence (P=0.021; OR=4.7), management safety empowerment (P=0.001; OR=8.36), management safety justice (P=0.034; OR=3.77), and workers' safety priority and risk non accepted (P=0.024; OR=5.64). Through the multivariate analysis, the results show that dimension which have the most association with safety behavior is management safety empowerment (P=0.014; OR=10.334) and workers' safety priority and risk non accepted (P=0.028; OR=8.365).